2000
DOI: 10.1016/s1527-6465(00)80038-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of pulmonary hypertension in patients undergoing liver transplant evaluation

Abstract: Clinical prediction of portopulmonary hypertension (PPHTN) is critical in the preoperative evaluation of candidates for orthotopic liver transplantation (OLT) because of its association with significant morbidity and mortality. To determine the clinical, laboratory, and echocardiographic predictors of PPHTN, we retrospectively evaluated 55 candidates before OLT. From those, 8 candidates had pulmonary hypertension ([HTN] group A) and 47 candidates did not (group B). Pulmonary HTN was defined as a mean pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…Based on the previous results of studies comparing preoperative and peroperative investigations, it has been suggested that, even if not specific, Doppler echocardiography when performed at evaluation is a reliable tool for detecting pulmonary hypertension. 5,6,10 An important finding in this study is that no significant correlation was found between preoperative and peroperative values of MPAP when measured by catheterization in patients who had or did not have portopulmonary hypertension. In contrast to what could be expected, MPAP was on average higher during the first phase of transplantation (under general anesthesia and before incision) than at evaluation in patients without portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Based on the previous results of studies comparing preoperative and peroperative investigations, it has been suggested that, even if not specific, Doppler echocardiography when performed at evaluation is a reliable tool for detecting pulmonary hypertension. 5,6,10 An important finding in this study is that no significant correlation was found between preoperative and peroperative values of MPAP when measured by catheterization in patients who had or did not have portopulmonary hypertension. In contrast to what could be expected, MPAP was on average higher during the first phase of transplantation (under general anesthesia and before incision) than at evaluation in patients without portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 60%
“…3 Because portopulmonary hypertension is frequently asymptomatic until mean pulmonary pressure exceeds 40 mm Hg, most authors recommend systematic screening at evaluation. Several studies have suggested that Doppler echocardiography, when performed during pretransplantation evaluation, is a useful noninvasive tool to document or exclude portopulmonary hypertension, [4][5][6] even though this technique carries a significant proportion of false positives. 5,6 However, in these studies, the results of Doppler echocardiography at the time of pretransplantation evaluation have been compared with those of catheterization at the time of surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20,21) The sensitivity and specificity of TTE or a diagnosis of PAH ranges from 0.79-1.0 and 0.60-0.98, respectively. 22) At our institution, we assign a value of 10 mmHg for RAP within the Bernoulli principle formula (PAP-TTE = TR-PG + RAP). However, even when assigning this value, TTE still overestimated PAP.…”
mentioning
confidence: 99%
“…При корреляци онном анализе выявлено, что степень выраженности одышки нарастала с утяжелением цирроза (r = 0,27; р = 0,01). Несмотря на то, что одышка, обнаружен ная при опросе больных, не является патогномонич ным симптомом при ЛАГ, тем не менее при физичес ких нагрузках это наиболее частый признак дебюта данного заболевания [18,20]. В связи с этим была проведена оценка одышки по шкале MRC у больных ЦП с наличием и отсутствием ЛАГ, результаты кото рой показали, что среди больных ЦП с признаками ЛАГ одышка была более выраженной (III-IV степе ни) в сравнении с пациентами без ЛАГ (I-II степе ни), что утяжеляет течение основного заболевания (р = 0,03).…”
Section: результаты и обсуждениеunclassified